Fatty Acid Composition of Mangrove Wild Legume Seeds (Sesbania speciosa) in Southwestern India - R. Sridhar, Kandikere; D. Anita, Dorothy; D. Ghate, Sudeep (Recent Patents on Food, Nutrition & Agriculture, 2016)
Background: This study compares the composition of fatty acid methyl esters (FAMEs) in seeds of Sesbania speciosa (dry and mature) after processing (uncooked and cooked) and extraction (hot and cold). Methods: Among PUFA, oleic, linoleic and linolenic acids were common to uncooked and cooked dry seeds which were high on cold extraction. Only two fatty acid ratios were favorable in hot extraction [(C14:0 + C15:0 + (C16:0 / C18:0) and C18:1 / C18:2]. Results: Cold extraction yielded docosahexaenoic acid in uncooked as well as cooked dry seeds and all fatty acid ratios were nutritionally favorable. In mature seeds, lauric and myristic acids were high on hot extraction, while palmitic and stearic acids were high on cold extraction. Except for ω-6/ω-3 ratio, the rest fatty acid ratios in mature seeds on hot extraction were not favorable, while cold extraction resulted in three favorable ratios (TUFA/TSFA, TPUFA/TMUFA and ω-6/ω-3). Three-way ANOVA on the impact of seeds, process and extraction of major fatty acids revealed significant difference only between extraction methods (p < 0.001). Conclusion: Overall, the cold extraction for dry as well as mature seeds were advantageous for essential fatty acids profile. Some of the recent patents are dealing with antineoplastic compounds as well as radioprotective drugs derived from Sesbania speciosa.
Keywords: mature seeds